Effectivity of ILF Neurofeedback on Autism Spectrum Disorder—A Case Study - Rauter, Alexandra; Schneider, Horst; Prinz, Wolfgang (Frontiers in Human Neuroscience, 2022)
Autism spectrum disorder (ASD) is a neural and mental developmental disorder that impact brain connectivity and information processing. Although application of the infra-low frequency (ILF) neurofeedback procedure has shown to lead to significant changes in functional connectivity in multiple areas and neuronal networks of the brain, rather limited clinical data is available for the efficacy of this technique in a therapeutic context to treat ASD. Here we present the case study of a five-year-old boy with ASD, who received a treatment of 26 sessions of ILF neurofeedback over a six-month period. A systematic and quantitative tracking of core ASD symptoms in several categories was used to document behavioral changes of time. The ILF neurofeedback intervention decreased the average symptom severity of every category to a remarkable degree, with the strongest effect (80% and 77% mean severity reduction) for physical and sleep symptoms and the lowest influence on behavioral symptoms (15% mean severity reduction). This case study shows that ILF neurofeedback is a practical and effective therapeutic instrument to treat ASD in children.